Fractal didactics in subject learning in the conditions of digital civilization - Ongarbayeva, Aliya; Kondubaeva, Mariyam; Kulgildinova, Tulebike; Ismakova, Bibissara; Tulkinbayev, Nurlan (E-learning and digital media, 2025)
The aim of the present study was to reveal modern approaches to the teaching process based on the principles of fractal didactics. This study reveals the concept of ‘fractal didactics and its influence on the educational process, subject teaching and personality development of future specialists. The principles of fractal didactics are defined and described, in particular: integration, self-similarity, openness, integrity, self. Such synergetic principles of personality development in the conditions of fractal didactics as: the principle of integrity, the principle of continuous development and the principle of balance are disclosed. The methods of fractal pedagogy include integrated as well as holistic learning, and their role in the educational process is described. The results of observation of the process of teaching Russian, Kazakh and English languages, built on the principles of fractal didactics, conducted on the basis of the Kazakh National Pedagogical University named after Abai, are presented. The results of the observation demonstrated that the basis of quality language training of future specialists in the conditions of digital society is the use of integrative and holistic approaches. It is concluded that fractal didactics can increase the effectiveness of subject teaching, in particular teaching Russian, Kazakh and English languages, in the conditions of digital civilization, as well as prepare students for continuous development. The levels of Benjamin Bloom’s taxonomy are described, on the basis of which the educational model of fractal didactics is developed. The most effective way to ensure the formation and development of the necessary skills is through an educational system that corresponds to the taxonomy model of fractal didactics, which was described in the framework of this study.